2018
DOI: 10.1038/nrd.2018.109
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the clearance of neurotoxic proteins in neurodegenerative disorders of ageing

Abstract: Neurodegenerative disorders of ageing (NDAs) such as Alzheimer disease, Parkinson disease, frontotemporal dementia, Huntington disease and amyotrophic lateral sclerosis represent a major socio-economic challenge in view of their high prevalence yet poor treatment. They are often called 'proteinopathies' owing to the presence of misfolded and aggregated proteins that lose their physiological roles and acquire neurotoxic properties. One reason underlying the accumulation and spread of oligomeric forms of neuroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
324
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(358 citation statements)
references
References 351 publications
(807 reference statements)
9
324
0
2
Order By: Relevance
“…Insufficient clearance of neurotoxic proteins by the autophagy-lysosomal network has been implicated in numerous neurodegenerative disorders 152 . In disorders such as AD, Huntington disease (HD) and PD, modi fied or misfolded proteins abnormally accumulate in specific regions of the brain.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…Insufficient clearance of neurotoxic proteins by the autophagy-lysosomal network has been implicated in numerous neurodegenerative disorders 152 . In disorders such as AD, Huntington disease (HD) and PD, modi fied or misfolded proteins abnormally accumulate in specific regions of the brain.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…It has also been reported that there is diurnal variation of iron content in the ventral midbrain (Unger, Earley, & Beard, 2009), supporting the existence of mechanisms for iron export from the brain to the systemic compartment. It has been suggested that the glymphatic system in the brain (Iliff et al, 2012;Papadopoulos & Verkman, 2013;Louveau et al, 2015;Trevaskis, Kaminskas, & Porter, 2015;Boland et al, 2018) may be one of the routes by which transition metals including iron are transported and cleared from the brain via convective bulk flow of interstitial fluid, possibly mediated by astrocytic end-feet-expressed aquaporin-4 (Aqp4) water channels (Ashraf et al, 2018). However, the available information about if and how this system facilitates iron transport remains limited at present and further studies are needed.…”
Section: Iron Transport Across the Blood-cerebrospinal Fluid Barmentioning
confidence: 99%
“…Neuronal proteostasis is continuously maintained by endoplasmic reticulum (ER)-mediated mechanisms including the unfolded protein response (UPR). Protein aggregates which are formed in spite of this are removed from neurons by autophagy [19,20]. In AD, ER function and autophagy are compromised due to both NFT buildup and A␤ accumulation [21].…”
Section: Introductionmentioning
confidence: 99%